High-energy Q-switched ytterbium-doped all-fiber laser with tris-(8-hydroxyquinoline) aluminum as saturable absorber - Salam, Sameer; Wong, Wei Ru; Al-Masoodi, A.H.H.; Harun, Sulaiman Wadi (Optical Society of America, 2019)
We have experimentally demonstrated a Q-switched fiber laser operating in the 1 μm region by using tris-(8-hydroxyquinoline) aluminum (Alq3) as a saturable absorber (SA). The Alq3 was fabricated through a drop-casting technique, where the material was embedded into a polyvinyl alcohol (PVA) film so that it can effectively incorporated into a laser cavity. The fiber laser has produced a high pulse energy of 0.8 μJ and peak power of 90mW. When the laser cavity was reduced from 25 m to 5 m, the peak power increased and the pulse energy dropped to 237.62mW and 451.5 nJ, respectively. Additionally, the minimum pulse width was reduced from 9 μs to 1.9 μs. © 2019 Optical Society of America.